2020
DOI: 10.21203/rs.3.rs-46748/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laboratory Test Ordering in Inpatient Hospitals: A Scoping Review on the Effects and Features of Clinical Decision Support Systems

Abstract: Background: Studies have revealed inappropriate laboratory testing as a source of waste. This review was aimed to evaluate the effects and features of CDSSs on physicians' appropriate laboratory test ordering in inpatient hospitals.Method: Medline through PubMed, SCOPUS, Web of Science, and Cochrane were queried without any time period restriction. The outcomes were categorized based on test-related, physician-related, and patient-related. The primary outcome measures were the number and cost of laboratory tes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Their findings showed that EHR-based interventions can moderately decrease inappropriate image ordering and decrease overall utilization of imaging by a small amount. Although, previous reviews 1 51 found that hard-stop CDSSs is more effective than other interventions, most of the CDSSs in our study provided recommendation based on patient indication, and just in a few cases, physicians had to justify overriding the recommendation. Hard-stop CDSSs prevent physicians from ordering an imaging until a confirmation is reached from an external member like a radiologist.…”
Section: Discussionmentioning
confidence: 67%
“…Their findings showed that EHR-based interventions can moderately decrease inappropriate image ordering and decrease overall utilization of imaging by a small amount. Although, previous reviews 1 51 found that hard-stop CDSSs is more effective than other interventions, most of the CDSSs in our study provided recommendation based on patient indication, and just in a few cases, physicians had to justify overriding the recommendation. Hard-stop CDSSs prevent physicians from ordering an imaging until a confirmation is reached from an external member like a radiologist.…”
Section: Discussionmentioning
confidence: 67%